Patterning and cell type specification in the developing CNS and PNS : comprehensive developmental neuroscience - Rubenstein, John L. R., 1955-; Rakic, Pasko, 1933- (Academic Press, 2013)
The genetic, molecular, and cellular mechanisms of neural development are essential for understanding evolution and disorders of neural systems. Recent advances in genetic, molecular, and cell biological methods have generated a massive increase in new information, but there is a paucity of comprehensive and up-to-date syntheses, references, and historical perspectives on this important subject. The Comprehensive Developmental Neuroscience series is designed to fill this gap, offering the most thorough coverage of this field on the market today and addressing all aspects of how the nervous system and its components develop. Particular attention is paid to the effects of abnormal development and on new psychiatric/neurological treatments being developed based on our increased understanding of developmental mechanisms. Each volume in the series consists of review style articles that average 15-20pp and feature numerous illustrations and full references. Volume 1 offers 48 high level articles devoted mainly to patterning and cell type specification in the developing central and peripheral nervous systems. Series offers 144 articles for 2904 full color pages addressing ways in which the nervous system and its components develop Features leading experts in various subfields as Section Editors and article Authors All articles peer reviewed by Section Editors to ensure accuracy, thoroughness, and scholarship Volume 1 sections include coverage of mechanisms which: control regional specification, regulate proliferation of neuronal progenitors and control differentiation and survival of specific neuronal subtypes, and controlling development of non-neural cells.